The abolitionists and the South, 1831-1861 - Harrold, Stanley (University Press of Kentucky, 1999)
Within the American antislavery movement that reached its peak during the thirty years before the Civil War, abolitionists were the most outspoken opponents of slavery. They were also distinct from other members of the movement in advocating, on the basis of moral principle, the immediate emancipation of slaves and equal rights for black people. Instead of focusing on the "immediatists" as products of northern culture, as previous historians have done, Stanley Harrold examines their involvement with antislavery action in the South - particularly in the region that bordered on the free states. How, he asks, did antislavery action in the South help shape abolitionist beliefs and policies in the period leading up to the Civil War? At the heart of this book is a dramatic story of individuals who, under the auspices of northern abolitionism, actively opposed slavery in the upper South. Harrold explores the interaction of northern abolitionists, southern white emancipators, and southern black liberators in fostering a continuing antislavery focus on the South, and integrates southern antislavery action into an understanding of abolitionist reform culture. He describes the risks taken by those northerners who went south to rescue slaves from their masters and discusses the impact of abolitionist missionaries, who preached an antislavery gospel to the enslaved as well as to the free. Harrold also offers an assessment of the impact of such activities on the coming of the Civil War and Reconstruction.